PO.8.185 Microvascular changes in systemic lupus erythematosus and systemic sclerosis. (27th September 2022) - Mazeda, C; Silva, S; Azevedo, S; Barcelos, A
Abstract : Purpose: Microvascular changes play central roles in the pathophysiology of systemic sclerosis (SSc) and systemic lupus erythematosus (SLE). Nailfold video-capillaroscopy (NVC) is a non-invasive and inexpensive tool that allows assess the microvascular involvement. In the last two decades, capillaroscopic patterns specific to SSc have been defined but in SLE only normal patterns and a variety of 'non-specific' capillary abnormalities have been observed. The aim of this study was to evaluate the association between capillaroscopic changes, organ involvement and laboratory findings SLE and SSc patients. Methods: A retrospective study was performed including SLE and SSc patients followed in outpatient rheumatology clinic. Socio-demographic and clinical data were collected. Descriptive analysis was performed; p-value≤0.05 was statistically significant. Results: 31 SLE (29 female; 2 men) and 24 SSc (19 female; 5 men) patients are included, averaging 46.96±13.80 and 58.42±11.38 years old with a mean disease duration was 10.93±7.65 and 3.58±2.63 years, respectively. In SLE patients, the most frequent involvements were hematological and cutaneous (70.1%). Only 19.4% of patients had Raynaud's phenomenon. All patients had positive ANAs (22.7% anti-dsDNA, 22.6% anti-Ro60, 12.9% anti-Ro52, 6.5% anti-SSB and 3.2% anti-Scl70) and 10% had positive antiphospholipid antibodies. In the capillaroscopy findings, all patients showed a normal pattern and alterations were observed in the morphology of the capillaries in 35.5% with tortuous capillaries and 6.5% with the presence of hemorrhages. We found statistically significant differences regarding morphology changes in NVC and hematological involvement as well as the SLEDAI score (p=0.044). In the case of SSc, 29.2% had the limited involvement and all patients had Raynaud's phenomenon (45.8% had a history of digital ulcers). Also, all patients had positive ANAs (58.3% anti-centromere, 25% anti-Scl70, 12.5% anti-RNA polymerase III and 8.3% anti-SSA) In capillaroscopy findings, all patients had a scleroderma pattern (50% early, 33.3% active and 16.7% late). History of digital ulceration, pulmonary involvement and positivity for anti-Scl70 were found to be statistically correlated with SSc pattern. When comparing SSc and SLE groups, significant differences were found between the pattern of NVC and Raynaud's phenomenon, as well as the presence of anti-Scl70. Conclusions: Microvascular changes are a prominent feature in both diseases and their assessment will be important in both diagnosis and follow-up. Findings in patients with SSc have already been demonstrated in previous studies but studies with larger sample sizes are warranted in patients with SLE with standardized capillaroscopic to clarify the role of NVC changes and the link between these and clinical or laboratory features.